Development of general nuclear resonance fluorescence model. Issue 11 (1st November 2016) - Ogawa, Tatsuhiko; Hashimoto, Shintaro; Sato, Tatsuhiko
ABSTRACT: A model to simulate nuclear resonance fluorescence (NRF) reactions of various nuclear species and their various excitation levels was developed. There is a strong need for the simulation of NRF applications using general purpose radiation transport codes; however, NRF reaction cross section data are available only for a few excited states for certain nuclear species. In this study, based on the generalized gamma de-excitation model, an NRF model that can simulate NRF reactions associated with all the levels included in the nuclear structure database was developed. Absorption cross sections calculated by the developed NRF model agree with the experimental data typically within one order of magnitude. To illustrate that this model can be used for simulation studies on NRF applications, the demonstration of the developed NRF model for non-destructive nuclear material assay and isomer production is shown.